Pattern of Injuries in Road Traffic Accident Death Cases in Western Haryana An Autopsy Study at Maharaja Agrasen Medical College, Agroha, Hisar (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Background: Fatal road traffic accidents (RTA) are a major cause of concern all over the world. The outcome of injuries sustained in an RTA depends on various factors including but not limited to: the location of the event, type of vehicle involved, nature of the roads, the time of accident, etc. Materials and Methods: The present study included all the fatal Road Traffic Accident cases, which had been brought to mortuary of Maharaja Agrasen Medical College during the period 1/02/2021 to 31/01/2022 with a sample size of 81 cases. Before and during conduction of postmortem examination, data was collected by using pre-designed semi structured proforma by the investigator himself. The data thus obtained was subjected to further suitable statistical analysis. Results: Among 81 cases, maximum deaths occurred in age group of 21-30 years and 82.7% were males. Most of the study participants (34.6%) were doing labour work. Approximately, 40% participants were brought dead in hospital. Among total victims, 46% were drivers, 23.5% were passengers, and 30.9% were pedestrians. About 55% of all deaths occurred in occupants of two wheelers. More than 85% victims experienced injuries on head. Fracture was the most common (85.2%) type of injury followed by abrasions (82.7%), lacerations (67.9%) and contusions (50.6%). The most commonly damaged internal organ was brain (~75%). The most common cause of death (48.2%) was head injury followed by complications due to head injury (9.9%), haemorrhage and shock due to multiple injuries (24.7%) and traumatic shock due to multiple injuries (12.4%). Conclusion: It may be concluded that there is urgent need to address the epidemic of RTA on the roads. Road traffic deaths are to a great extent preventable.
Keywords: Road traffic accidents; Injuries; Vehicles